“Urip Mung Mampir Ngombe”: Makna Peziarahan Hidup dalam Pemikiran Jawa dan Kristiani - Setiawan , Agustinus Devit; Kurniawan, Alphonsus Zeno (Perspektif, 2018)
'Urip mung mampirngombe', literally means 'life is just a visit to drink'. It is a Javanese saying which is frequently misinterpreted. It seems that everyone grown up in Javanese culure is determined to think pessimistically and behave nihilistically towards life. The writers argue that the old-aged saying as one element of the local wisdom should be interpreted in a right way. Surely, the saying has helped a lot of people to appreciate the worldly life seriously and promote the human culture religiously towards the life to come. Human beings are called towards the eternal life. Therefore, the worldly life is basically a pilgrimage. Such meaningful idea is then developed theologically that the faithful, particularly the Christians as Ecclesia peregrinans (pilgrim Church) (Ad Gentes 2), are called to work out their worldly lives wholeheartedlyfor the eschatological salvation (Lumen Gentium 48). Therefore, the 'mung mampirngombe' life is a serious pilgrimage towards the eternal one (cf. 1Tim 6:12).